Effect of Lactoferrin Derived from Bovine Colostrum on the Intensity of Peroxidative Processes in Liver Fragments Under their Hypothermic Storage - Sandomirsky, B. P.; Galchenko, S. E.; Galchenko, E. S. (Problems of Cryobiology and Cryomedicine, 2002)
The antioxidative (AO) activity of iron-binding protein lactoferrin (LF) derived from native and lyophilized bovine colostrum in the model of hypothermic storage of rat liver fragments has been studied. While estimating the lipid peroxidation (LPO) intensifying in membranes during cold storage of fragments, it has been shown that lactoferrin both from native and lyophilized colostrum has strong antioxidative effect and slows down the exhaustion of endogenous systems of antioxidative protection.